Adsorption of anionic dyes monoazo and diazo using organo-bentonite - Martínez Stagnaro, Susana Yamila (2019)
Adsorption of orangeand yellow dyes, containing mono- and di-azoic groups, respectively, werestudied by the use of a natural and organo-bentonite, which was obtained bytreatment with hexadecyl-trimethyl-ammonium bromide. Two different bentonitesfrom Argentina were used. X-ray diffraction, UV-visible spectrometry, infraredspectrometry and thermal analysis were used for the characterizations. Theresults were interpreted using isotherms that fit properly to the mathematicalmodel of Langmuir. The structural and physicochemical properties of the clay,and the arrangement of HDTMA+ in the interlayer of the smectites,the main clay mineral composition of the bentonites, were responsible for theretention of dyes. The retention of the azo dyes not only increased with theHDTMA+ modification of the bentonites but also depended on the claymineral (smectite types) composition of the pristine bentonite.